A new multiferroic ternary solid solution system of BiFeO3–Pb(Fe1/2Nb1/2)O3–PbTiO3. Issue 7 (July 2015) - Pang, Dongfang; He, Chao; Han, Shujuan; Pan, Shilie; Long, Xifa; Tailor, Hamel
Abstract: A ternary solid solution system of BiFeO3 –Pb(Fe1/2 Nb1/2 )O3 –PbTiO3 [BF–PFN–PT] has been synthesized in the form of ceramics by conventional solid reaction method in order to understand the systems multiferroic properties by investigating its structure, electric and magnetic properties. The introduction of Pb(Fe1/2 Nb1/2 )O3 (PFN) into the BiFeO3 –PbTiO3 (BF–PT) binary system can effectively decrease the coercive field ( E C ) of BF–PT system. The ternary system exhibits a coercive field, E C  = 5.2 kV/cm and enhanced piezoelectric properties with an optimal piezoelectric constant, d 33 of ∼351 pC/N at the composition of 0.25BiFeO3 –0.63Pb(Fe1/2 Nb1/2 )O3 –0.12PbTiO3 . The Curie temperature ( T C ) of BF–PFN–PT ceramics varies in the range of 309 to 146 °C. The temperature dependence of magnetization shows that the ternary system is of weak antiferromagnetic ordering with Neel temperature varying from 275 to 230 °C as shown by anomalies in the M – T curves.